Suppression of soil nitrification by plants; Plant Science; Vol. 233 - Subbarao G. V. Guntur Venkata; Yoshihashi Tadashi; Worthington M. Margaret; Nakahara Kazuhiko; Ando Yasuo; Sahrawat Kanwar Lal; Rao I. M. Idupulapati Madhusudhana; Lata Zh.-K. Zhan-Kristof; Kishii Masahiro; Braun Hans-Joachim (2015, 2015)
Title screen